Transient instant radiosity for efficient time-resolved global illumination. (October 2019) - Pan, Xian; Arellano, Victor; Jarabo, Adrian
Highlights: We generalize the classic work of instant radiosity, which is very suitable for parallelism in the GPU, to transient state. We show how to derive it from the transient path integral. We implement it on the GPU, using simplifications of the light transport process. Graphical abstract: Abstract: Over the last decade, transient imaging has had a major impact in the area of computer graphics and computer vision. The hability of analyzing light propagation at picosecond resolution has enabled a variety of applications such as non-line of sight imaging, vision through turbid media, or visualization of light in motion. However, despite the improvements in capture at such temporal resolution, existing rendering methods are still very time-consuming, requiring a large number of samples to converge to noise-free solutions, therefore limiting the applicability of such simulations. In this work, we generalize instant radiosity, which is very suitable for parallelism in the GPU, to transient state. First, we derive it from the transient path integral, including propagation and scattering delays. Then, we propose an efficient implemention on the GPU, and demonstrate interactive transient rendering with hundreds of thousands of samples per pixel to produce noiseless time-resolved renders.